Case Report: Experience and Lesson From Postpartum Ruptured Abdominal Aortic Aneurysm - Wang, Yumei; Tian, Di; Yang, Liu; Zhang, Qian; Qin, Guangyao; Liu, Xinghui (Frontiers in Medicine, 2022)
The incidence of abdominal aortic aneurysms in pregnant women is low. Because the disease is insidious, it is not easily recognized and is misdiagnosed by obstetricians. leading to serious adverse outcomes. Abdominal aortic aneurysm is one of the most dangerous diseases in the field of vascular surgery. Once the aneurysm ruptures, the disease progresses rapidly, and the fatality rate is extremely high. By retrospectively analyzing a rescue case of a ruptured abdominal aortic aneurysm after delivery, this study aims to draw attention to this disease and raise awareness amongst obstetric medical staff to recognize this condition in pregnant women. We report the experience and lessons learned from this case in order to improve the preoperative diagnosis and treatment rates, reduce the rate of missed diagnosis, and boost the prognosis for patients.